Analysis of Two Electrocution Accidents in Greece that Occurred due to Unexpected Re-energization of Power Lines - Aikaterini D. Baka; Nikolaos K. Uzunoglu (Elsevier, 2014)
Investigation and analysis of accidents are critical elements of safety management. The over-riding purpose of an organization in carrying out an accident investigation is to prevent similar accidents, as well as seek a general improvement in the management of health and safety. Hundreds of workers have suffered injuries while installing, maintaining, or servicing machinery and equipment due to sudden re-energization of power lines. This study presents and analyzes two electrical accidents (1 fatal injury and 1 serious injury) that occurred because the power supply was reconnected inadvertently or by mistake.